Content of Hematologic Malignancies Consultations: Good and Bad News From the HEMA-COMM Study - Lee, Stephanie J.; Sullivan, Amy; Goldman, Roberta E; Matsuyama, Robin; Loberiza, Fausto R.; Back, Anthony L; Alexander, Stewart C (Blood, 2009)
Abstract 68 Communications literature suggests that optimal doctor-patient communication in medical encounters should include several specific behaviors to enhance successful communication. Very little is known about how often hematologic malignancy subspecialists engage in these behaviors, but several studies have documented that patients are more optimistic about their prognoses than their physicians. We anticipated that a first consultation with a hematology-oncology subspecialist would provide an opportunity to study doctor-patient communication in a particularly intense situation, since the patient and physician are meeting for the first time, discussing a life-threatening disease, and usually confirming or deciding on a treatment plan. Methods and Subjects: We studied 236 patients having first consultations with 40 physicians at two academic institutions in the HEMA-COMM study. The HEMA-COMM study is an observational study designed to evaluate doctor-patient communication with data collected through patient and physician surveys, patient interviews, and audiotaping and coding of the consultations. Results: Median patient age was 55 years and 53% were men, 89% White, 78% married and 60% had at least a college education. Diagnoses included lymphoma (31%), acute leukemia (19%), myelodysplastic syndrome (17%), multiple myeloma (16%) and chronic leukemia (16%). Median age of physicians was 47 years and 85% were men. The median year of fellowship completion was 1992. Physicians estimated they saw a median of 8 new patients a month, 80% of whom were direct referrals. Results: Median duration of the consultations was 80 minutes. Coding of recorded consultations showed the frequency at which recommended communication behaviors occurred: discussion about purpose of the visit (78%), patient prior knowledge about disease (89%), patient preference for decision-making role (37%), patient understanding of presented information (31%), and patient preference for information (5%). Consultations addressed treatment recommendations (97%) and treatment impact on quality of life (52%), but rarely patient participation in recovery (1%). Qualitative prognostic information was provided in 97% of consultations and quantitative information in 90%, but “hedging” (suggestions that prognostic estimates do not apply to the individual) occurred in 23%. Overall, 64% of consultations included clear discussion of mortality risk without hedging and 49% included clear discussions of cure risk without hedging. The median number of patient questions was 23 (range 0-122). The percentage of patients with a treatment plan increased from 31% before the consultation to 79% after the consultation and 98% of patients were happy with their level of involvement in decision-making. Patients were satisfied with their consultations and 80% were very likely to recommend the consulting physician to other patients. Conclusion: Physicians could improve their verbal communication by assessing patients' preferences for information and decision-making roles, and checking for patient understanding during consultations. Approximately half of consultations in our study clearly addressed prognostic topics such as mortality and cure. These data form the basis for investigating factors which contribute to optimal doctor-patient communication about life-threatening disorders. No relevant conflicts of interest to declare.